Implementasi Program PBL (Pembangunan Berbasis Lingkungan) Mapaluse di Kota Manado. - Ransun, Toar Willem; Rumapea, Patar; Rares, Joyce Jecinta (Sam Ratulangi University, 2014)
PBL Mapaluse is one of the flagship programs of the Mayor ofÂ Manado. ImplementationPBLMapaluse in Manado Citywas runaccording to regulations, but there are stillproblemsthatoccur. The theoryisusedto analyzethe datausing theVanMeterandVanHornis standardsand objectives ofthe policy /measureand policy objectives, resources, the characteristics ofthe implementing organization, communication betweenrelevant organizationsandimplementation activities, dispositionorattitude ofthe implementers, social,economicandpolitical. Data sources ori n formants as many as 14 people. The conclusionthat can be drawnfromthe results ofthis study isthatin generalthe implementation ofa PBLMapaluseprograminthe cityof Manadoalready well althoughthere aresomeobstacles that occurboth internally and externally. Recommendationsandsuggestionsto the governmentpay more attention tothe speed ofthe disbursement, So there is nolongerdelayin the disbursementof fundsineach environment. KEY WORD : Implementatation of PBL Mapaluse